2023
DOI: 10.55905/oelv21n6-095
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise level exposures outside and inside agricultural tractor cabs

Abstract: The farm tractor fleet in the Brazilian market has increased. They are machines known to emit much noise. Noise can cause severe damage and disturbance in people who work directly with and around these machines. Therefore, the work aimed to evaluate the noise levels emitted by two cab farm tractors of different engine power, analyzing the effect of engine speed and distance radius from the noise source on occupational health. The noise level outside and inside of the tractor cab, the attenuation index, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The obtained values indicate that none of the investigated tractors produced a noise level higher than 80 dB(A), thus not exceeding the permissible limit. Souza et al [20] measured noise inside and outside the tractor on two tractors of different power. The obtained values did not exceed the permissible limit of 85 dB(A), and it was found that the TL85E tractor had lower measured values compared to the MF265 tractor.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained values indicate that none of the investigated tractors produced a noise level higher than 80 dB(A), thus not exceeding the permissible limit. Souza et al [20] measured noise inside and outside the tractor on two tractors of different power. The obtained values did not exceed the permissible limit of 85 dB(A), and it was found that the TL85E tractor had lower measured values compared to the MF265 tractor.…”
Section: Introductionmentioning
confidence: 99%